Unmaking the bomb:Environmental cleanup and the folitics of impssibility - Cram, Shannon (California California University Press, 2023)
Unmaking the Bomb investigates the politics of waste, exposure, and cleanup at the Hanford Nuclear Reservation, a former weapons complex in Washington State. Once the heart of American plutonium production, Hanford is now engaged in the nation's largest environmental remediation effort, managing toxic materials that will long outlast their regulatory containers. This book blends ethnographic research with personal narrative to examine cleanup's administrative frames and the stories that exceed them.